The Effect of Transformational Leadership on Team Performance on Construction Projects - Anto Purwadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This research aims to analyze the influence of transformational leadership on team performance in construction projects. In the construction industry, leadership effectiveness is a key factor influencing project success. This study uses a quantitative approach with a descriptive survey design, involving 150 respondents consisting of 30 project managers and 120 team members from various construction projects in Indonesia. Data was collected through a questionnaire that measured four dimensions of transformational leadership: ideal influence, inspirational motivation, intellectual stimulation, and individual consideration, as well as team performance based on timely task completion, quality of work results, and cost efficiency. The regression test results show that transformational leadership has a significant positive influence on team performance. The motivational dimensions of inspiration and ideal influence showed the highest correlation with team performance, with beta coefficients of 0.45 and 0.42, respectively (p < 0.05). The dimensions of intellectual stimulation and individual consideration also showed a positive influence with beta coefficients of 0.32 and 0.30 respectively (p < 0.05). Job satisfaction was found to be a significant intervening variable, where transformational leadership increased job satisfaction which then increased team performance. This research highlights the importance of implementing a transformational leadership style in construction projects to improve team performance. Recommendations include improving leadership competencies through training, increasing motivation and job satisfaction, encouraging innovation and creativity, and ensuring effective communication and building trust. By implementing this strategy, it is hoped that team performance in construction projects can improve, so that projects can be completed more efficiently and effectively. The results of this research provide practical insights for project leaders and managers in the construction industry to adopt transformational leadership to achieve optimal work results.